Economic Efficiency of Marketing Olive Crop in Region of (Al Salamia) (Journal of Hama University, 2020)
The aim of this study is to analyze the economic efficiency of marketing the Olive crop at the level of farmers and traders in the region of ​​( Al Salamia) and its villages, in order to determine the marketing performance and marketing problems facing farmers and traders of this crop, depending on a regular stratified sample consisting of(331) farmers and (10) retailers and (5) wholesalers and (2) export traders taken from the study area. It was also identified through the results of the study on the marketing pathways of the Olive crop and the marketing costs in those tracts. The marketing costs were at the level of farms (66.7) SP / kg, at the level of the wholesaler (49.3) SP / kg, and at the level of the retailer (29.2) SP / kg, where it is noted that retailers were the least in their marketing costs due to lack of marketing services such as the absence of commission cost.The highest marketing margin for olive oil was achieved by the export trader then the retailer and then the wholesaler (300,210,200) SP / kg, respectively. The results of the analysis showed significant differences between the wholesaler and the retailer for the total marketing costs of the Olive crop at a level of significance (0.01). As well as the existence of significant differences between different marketing routes for the total marketing costs of Olive oil at the level of significance (0.01). As for marketing efficiency, according to the first indicator, the marketing efficiency of the retailer (96.1%) was higher compared with the wholesaler (92.2%) and the export trader (92.03%). As for the second indicator, the marketing efficiency of the retailer (9.7%) was Compared with the rest of the patterns. It was found that the producers obtained the highest share of the wholesaler, which amounted to about (87.3%) of the wholesaler of oil and (85.3)% of Olive, while (86.02)% of the price of the retailer For oil and (82.05)% for Olives, And the lowest share of the product is from the export trader, where it reached about (72.72)% of the lira export dealer for Olive oil. The most important marketing problems were the high cost of transport, as 86.6% of farmers face this problem due to high fuel prices and maintenance of transportation.